Cholecystoduodenostomy Secondary to Common Bile Duct Obstruction in a Dog - Magalhães Jovani, Karen; Nunes Berger, Pietra; Peretti Guimarães, Fernando Peretti Guimarães; Gazza Romão, Felipe; Vieira Rossetto, Victor José (Acta Scientiae Veterinariae, 2025)
Background: Cholelithiasis is an obstructive syndrome of the hepatobiliary system associated with altered local homeostasis with thickening and slowing of the flow of bile, condensation of bile secretion, and formation of gallstones. Hepatopathy due to copper accumulation contributes to the formation of gallstones by breaking down cellular components through the synthesis of reactive oxygen species, damaging the hepatobiliary parenchyma and causing inflammation of the liver. This study aimed to report a surgical treatment that could re-establish extrahepatic biliary drainage in a canine patient with total ductal obstruction due to the presence of gallstones adhered to the lumen of the common bile duct. Case: A 7-year-old neutered male shih-tzu dog, weighing 9.9 kg, was attended with a history of chronic liver disease associated to hypercholesterolemia and hyperammonemia. Liver biopsy showed chronic hepatopathy due to copper accumulation. Additionally, the animal had episodes of emesis, apathy, anorexia, and abdominal pain. Blood count, biochemical, and imaging tests showed altered parameters, as increased hepatic enzymes. Abdominal ultrasonographic evaluation showed liver parenchyma permeated by various spherical and cavitary structures, and the gallbladder with hyperechogenic microstructures forming reverberations. Moreover, the topography of the cystic duct and common bile duct revealed dilatation of both, with hyperechogenic content forming superior acoustic shadowing. The changes indicate chronic hepatopathy, which is related to severe hepatic fibrosis, and an obstructive process of the gallbladder and bile ducts due to lithiasis. Surgical intervention was performed to resolve the cholestasis due to obstruction of the common bile duct, initially by duodenotomy, visualization of the duodenal papilla and unsuccessful choledochal catheterization. Due to this, it was performed cholecystoduodenostomy, effectively diverting, and redirecting the patient’s hepatobiliary flow by anastomosing the gallbladder to the descending duodenum. Five months after surgery, the animal was clinically well and had no pain or abdominal palpation. Discussion: The interruption of the flow of bile by gallstones into the biliary tract makes it progressively dilated. The patient in question had biliary concretion and obstructive biliary calculi, and the retained gallstones became progressively larger as the solutes concentrated. In the case of obstruction, the indication is catheterization and lavage of the common bile duct. During this maneuver, the gallstone is propelled into the gallbladder, which is then excised to prevent recurrence of the obstruction. However, this maneuver was not successful in this case report, as the gallstone was adhered to the wall of the common bile duct. Therefore, when it is not possible to restore the patency of the bile ducts, it is recommended to create an alternative route for the bile to redirect the bile flow. Cholecystoduodenostomy is currently an accepted technique for obtaining biliary enteric anastomoses in dogs. This procedure is only performed when the gallbladder is in good anatomical condition. Keywords: hepatopathy, hepatobiliary system, liver failure, cholelithiasis, enterobiliary, cholestasis.